The relationship between the level of vitamin D and ruptured intracranial aneurysms among patients with high sun exposure - Lívio Pereira de Macêdo; Renata de Castro Tavares; Mateus Torres Braga; Lidiane Moura dos Santos; Glaudir Donato; Fábio Antônio Serra de Lima Júnior; Rosanne Pereira de Macêdo; Arlindo Ugulino Netto; Kauê Franke; Pierre Vansant Oliveira Eugênio; Auricélio Batista Cezar-Junior; Igor Vilela Faquini; et al. (Scientific Reports, 2024)
Abstract Non-traumatic subarachnoid hemorrhage (SAH) accounts for 3–5% of acute strokes. Intracranial aneurysm is the most common cause of non-traumatic SAH. Vitamin D influences the cardiovascular system, including the formation and rupture of cerebral aneurysms. To evaluate the serum vitamin D level in patients living in the tropical zone who suffered aneurysmal subarachnoid hemorrhage and its correlation with demographic and neurological characteristics. This is an analytical cross-sectional study to assess the serum level of vitamin D in a study population of 99 patients treated and diagnosed with aSAH in a public hospital in Recife-PE over a period of 12 months. In the study sample, composed of individuals with high sun exposure due to the lifestyle they lead in a tropical region, we observed hypovitaminosis D (85.9%), with a median of 19.9 ng/ml, although the majority of individuals are skin with high concentration of melanin (Fitzpatrick skin type IV and V). In addition, rates of sun exposure are high to all patients (Solar Index 9.03 P50). Most individuals were female (79.8%); there was no statistical difference in solar exposure/solar index between genders. As for the neurological repercussions, there was no statistical relevance in the clinical prognostic scales evaluated. As the sample was composed mainly of individuals whose economic activity is agriculture, the values of solar index found are vastly higher than those of other studies conducted in high latitude regions. In line with the literature review, some aspects were raised with the objective of justifying such findings that go from the base of the poor diet of these individuals, the increase of melanin in the skin and genetic alterations that directs us to possible mechanisms of natural photoprotection to high sun exposure. Thus, we had a vast majority (85%) of hypovitaminosis D, which in fact makes us wonder if there is any influence of calcitriol on vitamin D receptors in vascular walls and in the cardiovascular system as a whole, which influence bleeding events of this nature. As for the neurological repercussions, measured using assessment scales (Glasgow coma scale, WFNS scale, Hunt–Hess and Fisher's tomographic scale) there was no significant difference in the results. As it is only a descriptive study, the causal relationship of the facts cannot be established. However, in a population exposed to high sun exposure and affected by aneurysmal SAH, there is a significant rate of hypovitaminosis D, which supports the hypothesis that vitamin D plays a role in vascular pathologies, such as cerebral aneurysms and SAH.